Pulmonary Lymphomatoid Granulomatosis With Hemophagocytic Lymphohistiocytosis as the Initial Manifestation - Xu, Li; Zhang, Xuan; Lu, Ying-Juan; Zheng, Yan-Hua; Gao, Guang-Xun (Frontiers in Oncology, 2020)
Lymphomatoid granulomatosis (LYG) is an extremely rare angio-centric and angio-destructive B-cell lymphoproliferative disease. Driven by Epstein-Barr virus (EBV), LYG predominantly involves the bilateral lungs. Commonly presenting as multiple nodules in the lung, pulmonary LYG can masquerade as various infectious diseases, vasculitis, lung cancer or other metastatic neoplasm. It is difficult to be diagnosed and is always neglected by clinicians. No standardized therapeutic regimens for LYG has been established yet now. Hemophagocytic lymphohistiocytosis (HLH), a life-threatening condition caused by abnormal activation of macrophages and T-cells, is characterized by fever, hepatosplenomegaly, pancytopenia, hypercytokinemia and the presence of hemophagocytosis within the bone marrow, liver, spleen, or other lymphatic tissue. We herein report a 55-year-old man with recurrent fever, severe jaundice and multiple high-density opacities and nodules in both lungs, who was finally diagnosed with pulmonary LYG(Grade 3) manifested with secondary HLH. Administration of HLH-1994 protocol led to the rapid control of the symptoms caused by HLH. Rituximab-based combination therapy was useful yet LYG(Grade 3) progressed rapidly. This case demonstrates that tissue biopsy is essential for early pathological diagnosis and effective treatment of LYG.